PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI PADA PT PELABUHAN INDONESIA IV (PERSERO) PETIKEMAS MAKASSAR - Ahmad Ridha; Guntur Suryo Putro (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2018)
The problem of this research is whether there is influence of compensation with indicator of giving service mark, health insurance, overtime allowance, giving of facility right, giving of charter of awards and giving praise to employee performance at PT Pelabuhan Indonesia IV (Persero) Makassar Container Terminal Branch? Data collection techniques in this study using observations and questionnaires. While the data analysis technique used is simple regression analysis. And the results showed that compensation on employees of PT Pelabuhan Indonesia IV (Persero) Makassar Container Terminal Branch has an influence on employee performance. And from the data processing SPSS 21, obtained a simple regression equation Y = 0.198 0.995 X. Keywords: Compensation, Employee Performance